Scavenger receptor B1 involvement in chronic obstructive pulmonary disease pathogenesis - Carlo Cervellati; Paolo Casolari; Alessandra Pecorelli; Claudia Sticozzi; Francesco Nucera; Alberto Papi; Gaetano Caramori; Giuseppe Valacchi (Bioscientifica, 2023)
Objective: Chronic obstructive pulmonary disease (COPD) is one of the main causes of morbidity and mortality in the United States. Oxidative stress due to cigarette smoking seems to be one of the major driving mechanisms in COPD pathogenesis. Since the scavenger receptor B1 (SR-B1) appears to play a key role in med iating the uptake for ɑ-tocopherol and other antioxidants in lung tissue, we aimed to investigate its role in COPD pathogenesis. Methods: Lung tissue biopsies were obtained from 12 subjects; 6 of these had a diagnosis of COPD in a stable clinical state, the others 6 were current (n = 1) or ex-smokers (n = 5) with normal lung function (controls). 4-Hydroxynonenal (4-HNE)-SR-B1 adducts were detected by immunoprecipitation. ɑ-tocopherol concentration was determined by HPLC. Results: SR-B1 levels were lower in COPD patients and these results par allel with lower levels of vitamin E in lung tissue found in COPD patients . This effect can be the consequence of oxidative posttranslational modifications, confirmed by the binding of the peroxidation product 4-HNE to SR-B1 possibly leading to its degradation. Conclusions: The loss of SR-B1 may be involved in lung ɑ-tocopherol content decrease with the consequence of making lung tissue more susceptible to oxidative damage as suggested by the SR-B1-4-HNE adduct formation, and more prone to COPD development. Thus, our findings suggest a novel role of SR-B1 in pathomechani sms underlying COPD. Significance statement Chronic obstructive pulmonary disease (COPD) is one of the main causes of morbidity and mortality in the United States. Oxidative stress has been suggested to be the major driving mechanism in COPD pathogenesis. Loss of scavenger receptor BI (SR-B1) significantly decreases tocopherol lung content making lung tissue more susceptible to oxidative damage. The results of our study show that SR-B1 levels were lower in COPD patients and these results parallel with lower levels of vitamin E in lung tissue. Our findings suggest a novel role of SR- B1 in pathomechanisms underlying COPD.